BnaA03.ANS Identified by Metabolomics and RNA-seq Partly Played Irreplaceable Role in Pigmentation of Red Rapeseed (Brassica napus) Petal - Hao, Pengfei; Liu, Han; Lin, Baogang; Ren, Yun; Huang, Lan; Jiang, Lixi; Hua, Shuijin (Frontiers in Plant Science, 2022)
Colorful flowers of rapeseed (Brassica napus L.) have been a hotspot for researchers, but the underlying mechanisms of pigment formation still need to be clarified. In this study, two stages of unopened rapeseed petals with red, white, and yellow colors were selected to identify the metabolites and genes involved in red pigment formation. Metabolomic analysis showed that flavonoids enriched the most co-differentially accumulated metabolites among all categories, and showed higher accumulation in red petal rapeseed than in white and yellow petal ones. RNA-seq analysis showed that among co-differentially expressed genes involved in red pigment formation, genes involved in anthocyanin (belonging to flavonoids) biosynthesis pathway were largely regulated by ANS, DFR, and UF3GT. The expression of those genes was higher in red petals of rapeseed than in white and yellow petals ones as well. Results of RNA interference of BnaA03.ANS in red rapeseed altered petal colors from raspberry red to beige red and zinc yellow under different interference levels, with the contents of pelargonidin, cyanidin, lutein, neoxanthin, β-carotene, and lycopene significantly decreased. However, overexpression of BnaA03.ANS in yellow rapeseed petals did not change the color of yellow petals. This study confirmed the important function of flavonoids, especially anthocyanins on red pigment formation, and for the first time, identified the irreplaceable role of BnaA03.ANS on red-flowered rapeseed.